2009
DOI: 10.1111/j.1472-765x.2008.02480.x
|View full text |Cite
|
Sign up to set email alerts
|

Sterilization effect of atmospheric plasma onEscherichia coliandBacillus subtilisendospores

Abstract: Aims:  Escherichia coli and Bacillus subtilis spores were treated with an atmospheric plasma mixture created by the ionization of helium and oxygen to investigate the inactivation efficiency of a low‐temperature plasma below 70°C. Methods and results:  An electrical discharge plasma was produced at a radio frequency (RF) of 13·56 MHz, connected to a perforated circular electrode with a discharge spacing of 1–15 mm. The discharge gas was helium with 0–2% oxygen. For the plasma treatment, a dried E. coli cell or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(60 citation statements)
references
References 9 publications
(20 reference statements)
8
48
0
2
Order By: Relevance
“…So the UV radiation generated by the plasma jet played a little role to bacterial inactivation, and which was consistent with Ref. [14].…”
Section: Devitalization By Plasma Jetsupporting
confidence: 84%
See 3 more Smart Citations
“…So the UV radiation generated by the plasma jet played a little role to bacterial inactivation, and which was consistent with Ref. [14].…”
Section: Devitalization By Plasma Jetsupporting
confidence: 84%
“…Therefore, this result clearly indicated the temperature was not responsible for B. subtilis inactivation in our experiment, and which was consistent with Refs. [13,14]. In addition, about ten percent of the bacilli reduced after 3 min UV radiation generated by plasma jet.…”
Section: Devitalization By Plasma Jetmentioning
confidence: 95%
See 2 more Smart Citations
“…The cell wall rupture has been additionally attributed by Laroussi et al, (2003) and Mendis et al, (2002) to electrostatic forces due to accumulation of charges at the outer surface of cell membranes. The morphological changes in E. coli cells treated with atmospheric plasma at 75W for 2 min as observed under an electron microscope by (Hong et al 2009), clearly revealed that the treated cells had severe cytoplasmic deformations and leakage of bacterial chromosome. These observations demonstrate the loss of viability of bacterial cells after plasma treatment.…”
Section: Action On Cell Components and Functionsmentioning
confidence: 99%